How can banks effectively stabilize their retail customers saving behavior? The impact of contractual rewards on saving persistence and cash flow volatility - Tobias Schlüter; Sönke Sievers; Thomas Hartmann-Wendels (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
We examine the saving behavior of banks retail customers. Our unique dataset comprises the contract and cash flow information for approximately 2.2 million individual contracts from 1991 to 2010. We find that contractual rewards, i.e., qualified interest payments, and government subsidies, effectively stabilize saving behavior. The probability of an early contract termination decreases by approximately 40%, and cash flow volatility drops by about 25%. Our findings provide important insights for the newly proposed bank liquidity regulations (Basel III) regarding the stability of deposits and the minimum requirements for risk management (European Commission DIRECTIVE 2006/48/EC; in Germany, translated into the MaRisk). Finally, the results inform bank managers how the price setting via deposit interests influences their funding.
Keywords: G01; G21; G28; 330